An index to new genera and species of Nematoda in Zootaxa from 2007 to 2012 - Xu, Yu Mei; Zhao, Zeng Qi; Wang, Jian Ming (Zootaxa, 2013)
Of 104 papers on nematodes published in Zootaxa from 2007 to 2012, seventy five, by 136 authors from 27 countries, described eight new genera and 155 new species. A bibliographic analysis of these papers and a list of new genera and species are presented in this paper.